Improving soil chemical properties by NPK fertilizer application and residual rice husk biochar effect on irrigation paddy field - Diana Samira; . Sufardi; . Zaitun; . Chairunas; Anischan Gani (Syiah Kuala University, 2013)
The research objective was to study effects of NPK fertilizer and biochar residue on soil chemical properties of paddy on second planting. Experiment was arranged in a randomized complete block design in a factorial design with four replications. Biochar consisted of two levels, i.e. without biochar residue and with biochar residue 10 ton ha-1. NPK fertilizer consisted of three levels, i.e. without NPK, NPK 60 kg ha-1, and NPK 120 kg ha-1. The result showed that application NPK fertilizer and biochar residue on second planting increase total N 22.22%, available P 12.18%, available K 17.50%, and organic C 56.69% compare than first planting